2020
DOI: 10.18805/ajdfr.dr-1499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Custard Apple (Annona squamosa) Seed Extract on Quality of Chicken Breast Fillets

Abstract: Chicken (Broiler) breast fillets were dipped separately for 10 min in distilled water, 100 ppm solution of BHT and 0.1, 0.3 and 0.5% aqueous solutions of custard apple (Annona squamosa) seed extract (CSE), stored under refrigeration (4±1oC) and analyzed on 0th, 3rd, 6th and 9th day of storage. Ascorbic acid content, Total Phenolic content, Ferric Reducing Antioxidant Power and DPPH radical scavenging assay of CSE were respectively 645.07±0.32 µgAA/mg, 234.30±0.44 µgGAE/mg, 882.95±0.34 µMFe(II)equi/g and 78.35±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…This result is similar to Al-Deen (2017) provided that among three different portions of A. squamosa fruit, peel showed the highest antimicrobial activity than pulp and seeds. In another study, Kadam et al (2018) reported similar results for peel extract of A. squamosa exhibited good antimicrobial activity against P. putida, S. putrefaciens, E. coli and E. fecalis with inhibition zones ranging from 10 -21 mm in increasing trend with increasing concentration of Annona squamosa peel extract from 250 to 1250 mg/ml. In a recent study of Kadam et al (2020), total phenolic and ascorbic acid content of hydroethanolic (50%) extract of Annona squamosa seed were respectively 234.30 ± 0.44 µgGAE/mg and 645.07 ± 0.32 µgAA/mg of the extract as a result of which possessed significant antioxidant as well as antibacterial activity.…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…This result is similar to Al-Deen (2017) provided that among three different portions of A. squamosa fruit, peel showed the highest antimicrobial activity than pulp and seeds. In another study, Kadam et al (2018) reported similar results for peel extract of A. squamosa exhibited good antimicrobial activity against P. putida, S. putrefaciens, E. coli and E. fecalis with inhibition zones ranging from 10 -21 mm in increasing trend with increasing concentration of Annona squamosa peel extract from 250 to 1250 mg/ml. In a recent study of Kadam et al (2020), total phenolic and ascorbic acid content of hydroethanolic (50%) extract of Annona squamosa seed were respectively 234.30 ± 0.44 µgGAE/mg and 645.07 ± 0.32 µgAA/mg of the extract as a result of which possessed significant antioxidant as well as antibacterial activity.…”
Section: Resultssupporting
confidence: 56%
“…In another study, Kadam et al (2018) reported similar results for peel extract of A. squamosa exhibited good antimicrobial activity against P. putida, S. putrefaciens, E. coli and E. fecalis with inhibition zones ranging from 10 -21 mm in increasing trend with increasing concentration of Annona squamosa peel extract from 250 to 1250 mg/ml. In a recent study of Kadam et al (2020), total phenolic and ascorbic acid content of hydroethanolic (50%) extract of Annona squamosa seed were respectively 234.30 ± 0.44 µgGAE/mg and 645.07 ± 0.32 µgAA/mg of the extract as a result of which possessed significant antioxidant as well as antibacterial activity. According to the results, all different part of extracts obtained from Annona squamosa shown to be with antibacterial activity against tested microbial pathogens.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations